1989
DOI: 10.1007/bf02212720
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of autism in Nagoya, Japan: A total population study

Abstract: The prevalence rate of autism has been reported as 0.04% to 0.05%, but one recent study in Japan found prevalence of 0.16%. The authors have been involved in routine well-child medical examinations at 18 months of age, at the Midori Public Health Center in Nagoya. A statistical survey of diagnoses was made from April 1979 to March 1984 for the purpose of conducting an epidemiological study of autism. Of 12,263 children examined, 168 were identified as having developmental problems and, of these, 139 underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(27 citation statements)
references
References 7 publications
0
23
0
4
Order By: Relevance
“…In a Japanese study by Sugiyama and Abe (1989) it was found that especially toddlers that failed a developmental check up at age 18 months, and whose parents refused further investigations, did show more developmental problems at 3-year follow-up than the children who did participate in further investigations. These results would suggest that the children who did not participate in the ESAT test might have had more serious disorders.…”
Section: Discussionmentioning
confidence: 94%
“…In a Japanese study by Sugiyama and Abe (1989) it was found that especially toddlers that failed a developmental check up at age 18 months, and whose parents refused further investigations, did show more developmental problems at 3-year follow-up than the children who did participate in further investigations. These results would suggest that the children who did not participate in the ESAT test might have had more serious disorders.…”
Section: Discussionmentioning
confidence: 94%
“…It also suggested that hesitation among parents could be reflected in the delay between screening and further examination of children. Sugiyama's study in Japan found that toddlers who failed a developmental check up at 18 months, and whose parents refused further investigations, showed more developmental problems at the 3-year follow up than the children who did participate in further investigations (Sugiyama & Abe, 1989). The present study included questions on parental concerns in screening in a general population in the UK.…”
Section: Parental Concern and Screening For Ascmentioning
confidence: 90%
“…We reviewed findings from six main sources: retrospective reports about the infancy of children who have received a diagnosis of autism (e.g., Dahlgren & Gillberg, 1989;Greenspan & Wieder, 1997;Lord, 1995;Stone & Lemanek, 1990); case studies of infants later diagnosed with autism (Dawson, Osterling, Meltzoff, & Kuhl, 2000;Sparling, 1991); analysis of early videotapes of infants eventually diagnosed with autism, including results from extensive work in our own laboratory (Baranek, 1999;Baranek et al, 2005;Eriksson & de Chateau, 1992;Osterling & Dawson, 1994); screening studies of high-risk clinical samples (Robins et al, 2001;Stone, Coonrod, & Ousley, 2000); prospective studies of infants who had an older sibling with autism (e.g., Zwaigenbaum et al, 2005); and prospective studies of a community sample (e.g., Baird et al, 2000;Baron-Cohen et al, 1996;Gillberg et al, 1990;Suqiama & Abe, 1989;Wetherby et al, 2004).…”
Section: Development Of the First Year Inventory (Fyi)mentioning
confidence: 99%